Matematyka

Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska

Wydawnictwo:WSiP

Rok wydania:2015

Ze wzoru wyznacz podaną zmienną 4.78 gwiazdek na podstawie 9 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

`a)` 

`e=mc^2\ \ \ \ |:c^2`  

`e/c^2=m` 

`m=e/c^2` 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`b)` 

`gamma=(nu)/f\ \ \ \ \ |*f` 

`gammaf=nu\ \ \ \ |:gamma` 

`f=(nu)/(gamma)` 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`c)`     

`s=nut+(at^2)/2\ \ \ \ |-nut` 

`s-nut=(at^2)/2\ \ \ \ |*2` 

`2s-2nut=at^2\ \ \ \ |:t^2` 

`(2s-2nut)/t^2=a` 

`a=(2s-2nut)/t^2` 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`d)` 

`r=(a+b-c)/2\ \ \ \ |*2` 

`2r=a+b-c\ \ \ \ |+c` 

`2r+c=a+b\ \ \ \ |-2r` 

`c=a+b-2r` 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`e)` 

`F=(GmM)/r\ \ \ \ |*r` 

`Fr=GmM\ \ \ \ |:GM` 

`(Fr)/(GM)=m` 

`m=(Fr)/(GM)` 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`f)` 

`K=(a-b)/c\ \ \ \ |*c` 

`Kc=a-b\ \ \ \ |+b` 

`Kc+b=a` 

`a=Kc+b` 

 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`g)` 

`P=(k+m)/k \ \ \ \ |*k` 

`Pk=k+m\ \ \ \ |-k` 

`Pk-k=m` 

`k(P-1)=m\ \ \ \ |:(P-1)` 

`k=m/(P-1)` 

 

`ul(ul(\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ ))` 

 

 

`h)` 

`N=(p-s)/(p+s)\ \ \ \ |*(p+s)` 

`N(p+s)=p-s` 

`Np+Ns=p-s\ \ \ \ |+s`  

`Np+Ns+s=p\ \ \ \ |-Np`  

`Ns+s=p-Np`  

`s(N+1)=p-Np\ \ \ \ \ |:(N+1)` 

`s=(p-Np)/(N+1)`